Increased co-morbidity of depression and post-traumatic stress disorder symptoms and common risk factors in intensive care unit survivors: a two-year follow-up study - Paparrigopoulos, T.; Melissaki, A.; Tzavellas, E.; Karaiskos, D.; Ilias, I.; Kokras, N (Int J Psychiatry Clin Practice, 2014)
OBJECTIVE: To investigate the long-term psychological impact of intensive care unit (ICU) hospitalization, as well as to establish risk factors which successfully discriminate patients at higher risk. METHODS: The Medical Outcomes Study Short Form Survey (SF-36), the Center for Epidemiologic Studies for Depression (CES-D), and the Davidson Trauma Scale (DTS) questionnaires were obtained from 48 ICU survivors who were also interviewed and self-reported on several acknowledged risk factors. RESULTS: A high co-morbidity between depression and post-traumatic stress disorder (PTSD) cases was observed. Both CES-D and DTS scores correlated negatively with the SF-36 mental health subscale scores; although a causative relation cannot be attributed to this finding, it indicates a potential negative impact of depression and PTSD symptoms on the patients' quality of life even at 18- to 24-month post-ICU. The most important risk factor associated with a long-term impact on quality of life, depression and PTSD was lifetime history of any psychiatric disorder. CONCLUSIONS: During ICU admissions efforts should be made towards identifying and psychologically supporting those patients with a previous history of a psychiatric disease, as they are at considerably higher risk of suffering from the long-term psychological sequelae of ICU admission.
Keywords: *Intensive Care Units; Adult; Analysis of Variance; Comorbidity; Depression/*epidemiology; Female; Follow-Up Studies; Hospitalization/statistics & numerical data; Humans; Life Change Events; Male; Mental Disorders/*epidemiology; Middle Aged; Quality of Life; Regression Analysis; Risk Factors; Socioeconomic Factors; Stress Disorders, Post-Traumatic/*epidemiology; Surveys and Questionnaires; Survivors/psychology/*statistics & numerical data